Drivers of competitiveness in the agricultural input sector: The case of agro-dealer businesses in Kenya - E. I. Wanyonyi; E. W. Gathungu; H. K. Bett (Cogent Business & Management, 2023)
Competitive pressure has resulted in fierce competition among agro-dealer businesses, with market share margins being divided among industry parti-cipants. This paper empirically investigates the main competitiveness drivers in Kenyan agro-dealer businesses. The study employed an exploratory research design, with primary data collected via face-to-face interviews from a sample of 110 agro-dealer businesses focusing on financial data for 2019. Business age, promo-tions strategies, entrepreneurship skills, and business expenditure were found to be positive competitiveness drivers, while competitive rivalry and branding were found to be constraining drivers. A policy to strengthen agro-dealer businesses' financial systems is an important step towards encouraging the adoption of new technology that will allow them to reduce operational costs while increasing revenues and ensuring proper resource utilization. Agro-dealer businesses should aim to increase their market share by utilizing promotions strategies (social media adverts, referral marketing and pull marketing) to both potential and prospective customers
Keywords: 650; Agricultural marketing; competitiveness; market share analysis and value chain analysis